Purchasing Decision Of Products On Marketplaces Reviewed From Consumer Trust, Product Quality, & Viral Marketi Development Of Msmes Through Innovation Of New Meatball Products "Sate Bakso Crispy And Pentol Tempe Kriuk" By Utilizing Social Media And Pr - Riska Wulan Ndari; Gustaf Naufan Febrianto, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This activity is a community service conducted in Surabaya for a micro enterprise (SME). The COVID-19 pandemic has had a direct negative impact on micro-enterprises in Indonesia, particularly in Surabaya. The implementation of Large-Scale Social Restrictions (PSBB) by both central and local governments significantly reduced consumer access to these micro enterprises. The aim of this community service is to enhance the knowledge and entrepreneurial skills of business owners in selling through social media platforms. This service is carried out through mentoring activities, including creating and training the use of social media for product sales, as well as monitoring and evaluation. The results obtained after the mentoring show an increase in consumer engagement with the micro-enterprise. This activity is expected to serve as an example for other micro-enterprises affected by the COVID-19 pandemic and provide a solution to the existing SME issues.